Green initiatives adoption and environmental performance of public listed companies in Malaysia - Abdul Aziz, Nor Azah; Ong, Tze San; Foong, Soon Yau; Senik, Rosmila; Attan, Hassan (MDPI, 2018)
Environmental issues bring about thoughtful questions on the roles of business organisations in society. Irrespective of whether they are contributing to a better environment or worsening it, organisations have to acknowledge environmental or green issues through impact research and measurement. This article aims to examine the extent of green initiatives adoption and its impact on environmental performance of public listed companies (PLCs) in Malaysia. A questionnaire survey was conducted on PLCs and data from 120 samples were analysed using a statistical tool partial least square-structural equation modelling (PLS-SEM). Interviews were also conducted with a few selected companies to obtain in-depth information on green practices and to support the survey findings. The findings reveal that the extent of green initiatives adoption and environmental performance is at moderate level. Green initiatives adoption positively affects the environmental performance of Malaysian PLCs. The present study contributes to the literature of environmental management in the context of green and sustainable development. It also provides some important contributions for management practices by providing empirical evidence to managers that green initiatives should be extensively adopted to enhance environmental performances.